1996
DOI: 10.1128/jvi.70.8.5083-5099.1996
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and evolution of adenovirus-associated RNA: a phylogenetic approach

Abstract: To explore the structure and function of a small regulatory RNA, we examined the virus-associated (VA) RNA species of all 47 known human adenovirus serotypes and of one simian virus, SA7. The VA RNA gene regions of 43 human adenoviruses were amplified and sequenced, and the structures of 10 representative VA RNAs were probed by nuclease sensitivity analysis. Most human viruses have two VA RNA species, VA RNA I and VA RNA II , but nine viruses (19%) have a single VA RNA gene. Sequence alignments classified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 69 publications
(125 reference statements)
6
48
0
Order By: Relevance
“…The nucleotide sequences between VAI and VAII RNAs of a particular virus are significantly different from one another. The same diversity can be observed when analyzing VAI or VAII among different serotypes, especially if they belong to different groups (A to F) [44,45]. Comparison of adenovirus serotypes has shown conserved regions in the 5′ end and near the 3′ terminus.…”
Section: Adenoviral-mediated Inhibition Of Rnai: Va Rnassupporting
confidence: 52%
See 3 more Smart Citations
“…The nucleotide sequences between VAI and VAII RNAs of a particular virus are significantly different from one another. The same diversity can be observed when analyzing VAI or VAII among different serotypes, especially if they belong to different groups (A to F) [44,45]. Comparison of adenovirus serotypes has shown conserved regions in the 5′ end and near the 3′ terminus.…”
Section: Adenoviral-mediated Inhibition Of Rnai: Va Rnassupporting
confidence: 52%
“…It has been shown that these sequences are required for VA RNA transcription initiation and termination. Besides these homologies, highly conserved sequences up to 4 nucleotides are present throughout the VA gene that seem to be required for maintenance of the VA RNA secondary structure [44,45].…”
Section: Adenoviral-mediated Inhibition Of Rnai: Va Rnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Virus-associated RNAs (VA RNAs) in AdVs are short, non-coding RNAs transcribed by RNA polymerase III to form double-stranded (ds) RNAlike secondary structures [14,15]. The number of VA RNA genes varies among different AdV species.…”
Section: Virus-associated Rnasmentioning
confidence: 99%